Peculiarities of treatment and prevention of recurrences in women with intrauterine pathologies - Okolokh Onieka Gibson; O. M. Makarchuk (Kazimierz Wielki University, 2021)
The study is devoted to the problem of surgical treatment, rehabilitation program and prevention of recurrences in intrauterine pathologies (polyposis and uterine adhesion) in women with reduced reproductive potential. The urgency of this problem is characterized by a high frequency of abnormal uterine bleeding, hypomenstrual syndrome and amenorrhea, infertility and miscarriage. Clinical data include the own experience of treatment and rehabilitation of 66 patients; women with intrauterine synechiae (32 people) were included in group 1; 34 patients with hyperplastic form of chronic endometritis and polyposis were included in group 2. The control group included 30 healthy patients without gynecological pathology and menstrual irregularities. All women underwent therapeutic hysteroscopy with adgeolysis and polypectomy. In the postoperative period, 24 patients of the main group received the proposed program to restore the endometrium and its implantation potential. The comparison group included 42 patients with general principles of postoperative management. The key points of the proposed program were: immunomodulatory therapy, hormone replacement therapy and the use of autoplasma. As a result of the study, a reduction in the recurrence of the adhesive process was proved, as well as a significantly higher number of cases of pregnancy. Thus, for the comprehensive treatment of intrauterine pathology in young women with reduced reproductive potential it is important not only to use minimally invasive office hysteroscopy, an active postoperative rehabilitation period is of great importance too.